Targeting carboxypeptidase A/B activity with the phosphinic inhibitor C28 reduces the asthmatic response in a mouse model of house dust mite-induced asthma - Allam, Venkata Sita Rama Raju; Montpeyó, David; Beau, Fabrice; Taha, Sowsan; Waern, Ida; Akula, Srinivas; Avilés, Francesc Xavier; Lorenzo, Julia; Devel, Laurent; Pejler, Gunnar; Wernersson, Sara (Inflammation research, 2025)
Objective Metallo-carboxypeptidases are implicated in several pathological contexts but their role in asthma and their potential as therapeutic targets in asthmatic settings are only partly understood. This study sought to investigate whether inhibition of carboxypeptidase activity of A and B-type could mitigate asthma-like symptoms in a mouse model of allergic airway inflammation. Methods BALB/c mice were sensitized and challenged with repeated intranasal instillations of 10 µg house dust mite extract. Prior to each instillation, groups of mice received intraperitoneally from 0.2 to 1 mg/kg of compound 28, a phosphinic inhibitor of A/B-type carboxypeptidases. Manifestations of asthma-like features were assessed, including airway hyperresponsiveness, airway inflammation, lung histopathology and inflammatory markers. Results Treatment with compound 28 protected against airway hyperresponsiveness and profoundly reduced the house dust mite-induced inflammation both in airways and in lung tissue. Moreover, compound 28 could mitigate airway smooth muscle and goblet cell remodelling as well as inflammatory gene expression in the lungs. Conclusions Compound 28 could suppress multiple features of asthma in a physiologically relevant mouse model, reinforcing the potential of targeting A/B type carboxypeptidases for therapeutic purposes in allergic asthma.